Development of Component 3A Tourism in the Youtefa Bridge Area, Jayapura City, Indonesia - Tandirerung, Bezaliel; Nuryanti, Wiendu (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
Tourism development has significant impacts on both the economy and the environment. This study aims to analyze the conditions and development of the 3A components of tourism (Attractions, Accessibility, and Amenities) around the Youtefa Bridge area in Jayapura following its construction in 2019. The background of this research is the strategic role of the Youtefa Bridge in enhancing the tourism potential of Jayapura, which has experienced significant growth since its completion. A qualitative descriptive method is used in this study, involving in-depth interviews, direct observation, and document analysis to collect comprehensive data. The steps in this method include data collection, data reduction, data presentation, and conclusion, so the data obtained can provide a comprehensive picture of the impact of the Youtefa Bridge construction on local tourism. The research findings show that the construction of the Youtefa Bridge has significantly improved accessibility and expanded tourism potential. The main attractions include natural beauty such as mangrove forests and beaches, as well as cultural attractions in Tobati Village and Enggros Village. The bridge itself has become a significant attraction, offering stunning views. Improvements in public transportation and road conditions now support better tourist mobility. Additionally, amenities around the Youtefa Bridge have been enhanced, with improved accommodation facilities, restaurants, and public facilities such as toilets and parking spaces. This study emphasizes the positive impact of the Youtefa Bridge on tourism development in Jayapura and the importance of sustainable tourism management to maintain the area’s appeal and ensure long-term benefits. Future research should focus on developing strategies to balance tourism growth with environmental conservation and cultural preservation.